Citizen Outsider : Children of North African Immigrants in France - Beaman, Jean, 1980- (Book collections on Project MUSE., 2017)
"While portrayals of immigrants and their descendants in France and throughout Europe often center on burning cars and radical Islam, Citizen Outsider: Children of North African Immigrants in France paints a different picture. Through fieldwork and interviews in Paris and its banlieues, Jean Beaman examines middle-class and upwardly mobile children of Maghrebin, or North African immigrants. By showing how these individuals are denied cultural citizenship because of their North African origin, she puts to rest the notion of a French exceptionalism regarding cultural difference, race, and ethnicity and further centers race and ethnicity as crucial for understanding marginalization in French society"--Provided by publisher.